PENGARUH MOTIVASI BELAJAR, MANAJEMEN KELAS DAN IMPLEMENTASI PROJECT BASEC LEARNING TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN - Sadaria Tamba; Pujianto Yugopuspito (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to show the positive effect of learning motivation on learning outcomes, the positive influence of classroom management on learning outcomes, the positive influence of project based learning (PBL) implementation on learning outcomes in Civic Education lessons in class VIII SMPS Harvest Christian School Tangerang. The research method used is descriptive analysis method that involved the entire population, namely 26 respondents in class VIII SMPS Harvest Christian School Tangerang. Data was collected using a survey method in the form of a closed questionnaire and a test in the form of a rubric. Data analysis used descriptive statistics, with inferential statistics, and hypothesis testing using SmartPLS version 3.0. This study shows that (a) learning motivation has a positive effect on student learning outcomes; (b) classroom management has a positive effect on student learning outcomes; c) PBL implementation has a positive effect on student learning outcomes in Civic Education learning.